Analisis Minat UMKM Terhadap Wakaf Produktif Di Surakarta - Aryakusuma Sumarjoko, Achmad; Sholahuddin, Muhammad (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of knowledge about productive waqf and trust in waqf managers on the perception of economic benefits and the interest of Micro, Small, and Medium Enterprises (MSMEs) in participating in productive waqf in Surakarta. The research employs a quantitative approach using a survey method. Data were collected from 191 MSME respondents selected through purposive sampling and analyzed using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method with SmartPLS 4.0 software. The results indicate that knowledge about productive waqf has a positive and significant effect on both the perception of economic benefits and the interest of MSMEs in productive waqf. Trust in waqf managers also shows a positive and significant influence on the perception of economic benefits and MSME interest. Furthermore, the perception of economic benefits has a positive and significant effect on MSME interest in productive waqf and acts as a partial mediating variable in the relationship between knowledge and trust toward MSME interest. The findings of this study affirm that improving knowledge and trust in waqf management institutions can strengthen the perception of economic benefits, which in turn increases MSMEs’ interest in participating in the development of productive waqf in Surakarta.